Changes in Potato Production and Consumption in Poland in 2001-2020 - Anna Kowalska; Klaudia Gurkowa (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the article is to analyse and assess changes in the potato market in Poland. The area of potato cultivation in Poland is gradually decreasing. The scale of this phenomenon is very large - unparalleled in any other country. Unprocessed, fresh potato are replaced more and more often with ready-made preserves and cereal products, e.g. groats, rice and pasta. The study uses statistical materials published by The Institute of Agricultural and Food Economics - National Research Institute and the Central Statistical Office. The time range of these data covers the years 2001-2019. During the development of the data, the basic methods of statistical analysis were used, i.e. correlation, change dynamics, arithmetic mean and standard deviation.